Tamanho ótimo de parcela na experimentação com plantas de macieira de baixa exigência em frio - Ribeiro, Gleick Cruz (2023)
Improvement work on the apple tree, carried out in various parts of the world, has resulted in the release of dozens of cultivars annually. Among the available cultivars, those that are not very demanding in terms of cold stand out, allowing their cultivation to be carried out in different geographic regions from those where the other varieties are cultivated. The cultivation of apple trees in the tropical conditions of the north of the state of Espírito Santo is recent and in order to increase the cultivation area, basic research in the area of field experimentation is still necessary. Thus, the objective of this work was to determine the optimum plot size for experiments with low-colddemanding apple trees of the Eva, Julieta and Princesa varieties, based on evaluation data for three traits in three-year-old adult plants in the north of the state of Espírito Santo. A blank trial was carried out containing the evaluation of 100 plants of each variety in three side-by-side rows. The plants were grafted in Marubakaido. Three years and three months after planting, the stem diameter, production in number of fruits per plant and in mass per plant were evaluated. Modified maximum curvature methods were used, in their original form according to Meier and Lessman and with bootstrap simulation to determine the optimal plot size. The Meier and Lessman methods and bootstrap simulation showed similar results for each trait, but the productive traits showed a greater optimal plot size than the vegetative trait of stem diameter. When setting up field experiments with apple trees of the varieties Eva, Julieta and Princesa in conditions in the north of the state of Espírito Santo, planning is recommended to have at least six plants in each experimental plot.